Dermal type I collagen assessment by digital image analysis - Gabrielli Brianezi; Fabrizio Grandi; Ediléia Bagatin; Mílvia Maria S. S. Enokihara; Hélio Amante Miot (Sociedade Brasileira de Dermatologia, 2015)
AbstractType I collagen is the main dermal component, and its evaluation is relevant to quantitative studies in dermatopathology. However, visual gradation (0 to 4+) has low precision and high subjectivity levels. This study aimed to develop and validate a digital morphometric analysis technique to estimate type I collagen levels in the papillary dermis. Four evaluators visually quantified (0 to 4+) the density of type I collagen in 63 images of forearm skin biopsies marked by immunohistochemistry and two evaluators analyzed the same images using digital morphometric techniques (RGB split colors (I) and color deconvolution (II)). Automated type I collagen density estimation in the papillary dermis (two techniques) were correlated with visual evaluations (Spearman's rho coefficients of 0.48 and 0.62 (p<0.01)). With regard to the inter-observer repeatability, the four evaluators who used visual classification had an intraclass correlation coefficient (for absolute agreement) of 0.53, while the other two evaluators who used digital analysis (algorithm II) had an intraclass correlation coefficient of 0.97.